Metode Resitasi Berbasis Tik Sebagai Upaya Penguatan Karakter Mahasiswa - I Made Arsa Wiguna (Jayapangus Press, 2018)
This paper aims to describe the role of ICT-based recitation method as an effort to strengthen student's character. Character education actually is very prevalent among educators, learners and the wider community. Strengthening character education is formulated in the curriculum of 2013 or more popularly known as K13. The scoring system is different ie authentic assessment. Educators seek to foster and strengthen character education through innovative learning models. Similarly in college, educators (lecturers) are required to have innovation power in the learning process. One of them through the use of ICT-based recitation method to strengthen the character of college students. Through this method, there are some characters that are trained to be stronger, such as religious, honest, responsibility, discipline, hard work, creative, like to read, and environmental care.